PANIC MORALS AND ANTI-BULLYING EDUCATION MANAGEMENT ON VIRTUAL MEDIA FOR SCHOOL CHILDREN: A CASE STUDY IN LOMBOK WEST NUSA TENGGARA, INDONESIA - Badrun (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Moral panic refers to the excessive reaction of society to certain issues, which is considered a threat to morality and public welfare triggered by virtual media that depicts an event or group in a sensational way, thereby triggering excessive fear and anxiety among the public. Bullying is a desire to hurt so that it causes a person to suffer. A bulliying perpetrator can be a person, a group of people, and he or they perceive themselves to have the power to do anything to their victims. This paper uses a qualitative method with a netnography approach. This approach is used to understand individual behavior and interactions in online contexts, such as communities, social networks, forums, or other platforms related to bullying in school children in Lombok NTB. The theory used is the social learning theory from Albert Bandura. This concept emphasizes that behavior is learned through observation, imitation, and modeling. In the context of moral panic and the management of anti-bullying education in school children in Lombok NTB, this theory suggests that children can learn bullying or anti-bullying behavior through examples they see around them, especially in virtual world life. The findings of this paper reveal that virtual media often report cases of bullying in a dramatic way, creating the perception that bullying is a major crisis that threatens the well-being of school children. Then excessive action against the bullying phenomenon leads to moral panic to immediately disseminate information. The dissemination of inaccurate information is a new sign that people in Lombok NTB suffer from moral panic syndrome.